Pementasan Kethoprak Penangsang Gugur: Hegemoni Jawa Mataraman dalam Kesenian Tradisional Jawa - Sukarjo Waluyo (Endogami: Jurnal Ilmiah Kajian Antropologi, 2021)
Solo is known as the hometown of kethoprak art. Kethoprak is classified into two types based on geographical reasons and performance characteristics, namely Pati kethoprak Pati(coastal) and kethoprak Solo-Jogja (Mataraman). The stories in Kethoprak Mataraman generally come from Babad Tanah Djawi. In this case, the version of the inland Javanese ruler is very visible. Through the character Arya Penangsang, kethoprak Mataraman seems to build a hegemonic representation. The hegemonic representations of kethoprak Mataraman in the Penangsang Gugur stage, first, Arya Penangsang is depicted as a power hungry character. Second, Sunan Kudus is described as an unjust and cunning teacher. Third, Arya Penangsang was described as a rebel for the Sultanate of Pajang. Fourth, the establishment of the Pajang Sultanate in inland Java as the successor to the Demak Sultanate.